1998
DOI: 10.1097/00004872-199816060-00016
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of combined converting enzyme inhibition and angiotensin II antagonism on blood pressure in conscious telemetered spontaneously hypertensive rats

Abstract: These results demonstrate that combination therapy aimed at interrupting operation of the renin-angiotensin system simultaneously at multiple sites can prevent the partial escape which occurs during chronic angiotensin converting enzyme inhibitor monotherapy. Furthermore, multiple-site intervention results in a more efficacious antihypertensive response than that achieved with high doses of the individual monotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 30 publications
4
43
1
Order By: Relevance
“…valsartan has no important effect on blood pressure is also supported by previous reports from other laboratories, 13,14 including telemetric measurements performed by Webb et al 14 These authors reported only minute effects of a somewhat higher dose of valsartan, 0.5 mg · kg…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…valsartan has no important effect on blood pressure is also supported by previous reports from other laboratories, 13,14 including telemetric measurements performed by Webb et al 14 These authors reported only minute effects of a somewhat higher dose of valsartan, 0.5 mg · kg…”
Section: Discussionsupporting
confidence: 76%
“…14 In the absence of telemetric measurements, we cannot exclude such minute effects in our study, but we consider it highly unlikely that the massive effects of valsartan on survival can be explained solely by lowering of the mean arterial blood pressure by some 5 mm Hg. Interestingly, blockade of the renin-angiotensin system was reported to improve survival in scleroderma renal crisis, 15 another form of thrombotic microangiopathy in the kidney.…”
Section: Discussionmentioning
confidence: 93%
“…However, the effects of combination therapy on cardiac gene expression have not been examined in previous reports. 6,7,22 Therefore, here, we investigated cardiac gene expressions and found that the combination of low doses of an ACE inhibitor and an AT 1 receptor antagonist (0.2 mg/kg each) decreased cardiac mRNA levels for ANF, collagen type I, and skeletal ␣-actin more potently than amlodipine alone. Furthermore, the combination of 0.05 mg/kg perindopril and candesartan cilexetil, whose hypotensive effects were similar to those of low doses of amlodipine combined with perindopril or candesartan cilexetil and were lesser than those of high doses (3 mg/kg) of amlodipine alone (Table 2), decreased left ventricular weight and ANF mRNA levels more potently than combination therapy or monotherapy with amlodipine.…”
Section: Discussionmentioning
confidence: 91%
“…Changes in blood pressure from baseline were analyzed by comparison of the areas over the curve, as calculated by the trapezoidal method (millimeters of mercuryϫdays). 17,18 Data obtained with the Langendorff preparation were recorded and digitalized using WinDaq waveform recording software (Dataq Instruments). After manual selection of the desired signals preinjection and postinjection, data were analyzed using Matlab (Mathworks Inc).…”
Section: Discussionmentioning
confidence: 99%